Trapping of branched DNA in microfabricated structures. - Volkmuth, W D (1995)
We have observed electrostatic trapping of tribranched DNA molecules undergoing electrophoresis in a microfabricated pseudo-two-dimensional array of posts. Trapping occurs in a unique transport regimen in which the electrophoretic mobility is extremely sensitive to polymer topology. The arrest of branched polymers is explained by considering their center-of-mass motion; in certain conformations, owing to the constraints imposed by the obstacles a molecule cannot advance without the center of mass first moving a short distance backwards. The depth of the resulting local potential well can be much greater than the thermal energy so that escape of an immobilized molecule can be extremely slow. We summarize the expected behavior of the mobility as a function of field strength and topology and point out that the microfabricated arrays are highly suitable for detecting an extremely small number of branched molecules in a very large population of linear molecules.